The insertion of afro-brazilian hystory and culture in everyday school life: a case study - Davi Silvestre Fernandes Martins; Leila Maria Ferreira Salles (Educação: Teoria e Prática, 2014)
This research investigates the implications of mandatory of thematic study of Afro-Brazilian history and culture in school daily life. It aims to analyze to what extent the promulgation of a specific law can modify relations established at school. The data from this case study were collected through questionnaires, interviews, observation, document analysis and focus groups. The analysis indicates that prejudices and biased relations still exist and determine conflicting relations on which educators generally tend to omit themselves. However, the review also indicated that the performance of the school can contribute to change the students' way of thinking and acting, thus collaborating for changing the social reality and the relations established in school daily life.